Business management & prophetic leadership - Badi, Jamal Ahmed Bashier (2017)
An overview of past discussions: (some ideas to be quoted) Interesting 1. One major problem with this course so far is that it has been viewed from ethical perspective (niyyah) and no concrete guidance on how to successfully run a business in real life. This course till now neglected the pragmatic guidance that the prophetic leadership gives. My speech today will shine a light on this missing pragmatic aspect. Many people would be keen to learn how to run a successful company based on the prophetic leadership guidance. To do this we shouldn’t limit our scope to ethical but should look at the practical side as well. 2. Liberals claim that the Sirah is only gives moral advice and does not tell us how to deal with contemporary issues and the struggle for the daily life. It is hoped that this speech will help us with Allah’s help and support to deal practically with the challenges we run into our current time and society.